Strategi Pengembangan Usahatani Bawang Merah (Allium Ascalonicum L) di Kebun Praktek Fakultas Teknologi Pangan Pertanian Dan Perikanan Universitas Nusa Nipa Maumere - Tapo, Theresia Barek (Jurnal Ilmiah Wahana Pendidikan, 2024)
Shallots (Allium Ascalonicum L) is a horticultural crop commodity that has high economic value which has long been intensively cultivated by farmers and is generally widely consumed by the public as a spice vegetable or better known as a food seasoning. This research aims to identify internal and external factors and determine strategies for developing Shallot Farming in the UNIPA FTP3 Practice Gardens from August 2023 to December 2023. Determining 20 respondents using Purposive Sampling Technique. This research uses a descriptive analysis method to determine SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) to look at the internal environment, namely strengths and weaknesses, as well as the external environment, namely opportunities and threats for shallot farming in the UNIPA Practice Farm. The results of this research show that the strategy analysis diagram of the Shallot Farming Business in the UNIPA Practice Garden is in quadrant I (Progressive), which means the Shallot Farming Business is in a profitable position and it is recommended to continue to expand, increase growth and achieve maximum progress. S-O's alternative strategy for Shallot Farming is to utilize strategic locations to increase shallot production so that it is marketed on a wider scale. W-O's strategy is more about utilizing public awareness to form new online-based markets by having labels, packaging and permanent markets. The S-T strategy improves the quality of shallots so that they are better than shallots from other regions. W-T's strategy seeks promotion and has a permanent label, packaging and market so that it can increase consumer attractiveness for organic shallot products.